2014
DOI: 10.3109/09537104.2014.959914
|View full text |Cite
|
Sign up to set email alerts
|

COMparison ofPlatelet reactivity following prAsugrel and ticagrelor loading dose inST-Segment elevation myocardial infarctIONpatients: The COMPASSION study

Abstract: Prasugrel and ticagrelor are potent P2Y12-ADP receptor antagonists which are superior to clopidogrel in acute coronary syndromes. To date no clinical trial directly compared these two drugs. Platelet reactivity correlates with ischemic and bleeding events in patients undergoing percutaneous coronary intervention. Recent pharmacological studies have observed a delayed onset of action of these two drugs in ST-segment elevation myocardial infarction (STEMI). We provide the first adequately powered pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…In the present study, the number of patients exhibiting HTPR as defined in an international consensus value was low (5.3%) and the number of patients with LTPR was high (55.8%). These rates are consistent with those in the literature, and they confirm the high potency of the drug, which was associated with a lower rate of HTPR compared to prasugrel in a recent study . In addition in our cohort, no baseline characteristic was associated with HTPR on ticagrelor, unlike what was observed with on‐clopidogrel PR, which is influenced by several factors.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the present study, the number of patients exhibiting HTPR as defined in an international consensus value was low (5.3%) and the number of patients with LTPR was high (55.8%). These rates are consistent with those in the literature, and they confirm the high potency of the drug, which was associated with a lower rate of HTPR compared to prasugrel in a recent study . In addition in our cohort, no baseline characteristic was associated with HTPR on ticagrelor, unlike what was observed with on‐clopidogrel PR, which is influenced by several factors.…”
Section: Discussionsupporting
confidence: 55%
“…These rates are consistent with those in the literature, 17 and they confirm the high potency of the drug, which was associated with a lower rate of HTPR compared to prasugrel in a recent study. 18 In addition in our cohort, no baseline characteristic was associated with HTPR on ticagrelor,…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Prasugrel is a third generation thienopyridine that irreversibly inhibits the platelet P2Y 12 receptors while ticagrelor is a cyclopenthyltriazolo-pyrimidine and a reversible antagonist of this receptor. To date, no study has directly compared ticagrelor and prasugrel regarding clinical outcomes, and small biological studies comparing the effect of both treatments on platelet reactivity have shown contradictory results [8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Thus, it remains uncertain whether or not one agent is superior to another regarding on-treatment platelet reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Alexopoulos et al, 27 STEMI patients treated with prasugrel presented 11.5% HTPR 6 h after loading dose administration and 0% 5 days after the treatment initiation, as assessed with the VeryfyNow P2Y12 assay [36]. Similarly, in a study conducted by Laine et al with 44 STEMI patients treated with prasugrel, HTPR measured 6-12 h after a loading dose of prasugrel and defined as VASP index above or equal to 50%, was reported in 4 patients (9,1%) [37]. Prasugrel was also shown to be effective in 44 ACS patients exhibiting HTPR following a clopidogrel loading dose.…”
Section: Discussionmentioning
confidence: 92%